HUBUNGAN JENIS KELAMIN DAN PEMINATAN DENGAN KELULUSAN UJI KOMPETENSI MAHASISWA NERS STIKES JENDERAL ACHMAD YANI YOGYAKARTA - Syah, Deby Zulkarnain Rahadian Syah; Riyadi, Sujono (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Competence test is a process of measuring the knowledge, skill, and behavior of learners in Mid-Level Expert in Nursing or Nurse Profession at the end of their study period to reach the competency standard of graduates a job competency standard. Graduation of competency test nurse student to 68,61%, indicating that there is 31,39% which not yet competent. The aim of research is to analyze the relationship of gender and student interest with graduation of competency test of nurse students. The research type is descriptive correlation with cross sectional approach. The research was conducted at Stikes General Achmad Yani Yogyakarta. The results showed that men slightly greater the number of graduates of nurse competence test than women. 11 competent men and 10 competent women. The statistical test results obtained p-value 1.00 shows no relationship between sex with the passing of competence test nurse. This study also resulted that the Nurse student program is not related to the passing of nurse competence test with p-value 0.976. Therefore, both male and female ners should still study the theory in every phase.